Assessment of the thermomechanical performance of continuous glass fiber-reinforced thermoplastic laminates. (May 2018) - Nikforooz, M.; Montesano, J.; Golzar, M.; Shokrieh, M.M.
Abstract: The effects of temperature on the static tensile behavior of continuous E-glass/polyamide laminates were studied in order to assess the feasibility of using the material system for structural applications. Uniaxial tensile tests were conducted on [0]8, [90]8, [02 /902 ]s and [04 /904 ]s laminates at multiple temperatures above and below the glass transition temperature, which was measured using different methods. Optical and scanning electron microscopy were performed on the tested samples, and the effects of temperature on failure modes were investigated. The [0]8 and [90]8 laminates displayed three reduction stages in modulus versus temperature, where the largest reduction was in the glass transition region as a result of notable softening of the polyamide matrix, as confirmed by fractographic analysis. However, the [02 /902 ]s and [04 /904 ]s laminates displayed the largest modulus reduction prior to the glass transition temperature with little reduction beyond, which was attributed to matrix softening coupled with in situ ply constraining effects. Highlights: The thermomechanical behavior of continuous E-glass/polyamide composites was investigated in lamina and laminate level. Glass transition temperature of the material was measured with DSC, TMA and DMA. [0]8 and [90]8 laminates displayed the largest modulus reduction in the glass transition region. [02 /902 ]s and [04 /904 ]s laminates displayed the largest modulus reduction prior to the glass transition temperature. Effects of temperature on material failure were investigated using optical and scanning electron microscopy.